Isolation and Characterization of the cis-trans-Unsaturated Fatty Acid Isomerase of Pseudomonas oleovorans GPo12 - Pedrotta, Valerian (American Society for Microbiology, 1999)
Pseudomonas oleovorans contains an isomerase which catalyzes the cis-trans conversion of the abundant unsaturated membrane fatty acids 9-cis-hexadecenoic acid (palmitoleic acid) and 11-cis-octadecenoic acid (vaccenic acid). We purified the isomerase from the periplasmic fraction of Pseudomonas oleovorans. The molecular mass of the enzyme was estimated to be 80 kDa under denaturing conditions and 70 kDa under native conditions, suggesting a monomeric structure of the active enzyme. N-terminal sequencing showed that the isomerase derives from a precursor with a signal sequence which is cleaved from the primary translation product in accord with the periplasmic localization of the enzyme. The purified isomerase acted only on free unsaturated fatty acids and not on esterified fatty acids. In contrast to the in vivo cis-trans conversion of lipids, this in vitro isomerization of free fatty acids did not require the addition of organic solvents. Pure phospholipids, even in the presence of organic solvents, could not serve as substrate for the isomerase. However, when crude membranes from Pseudomonas or Escherichia coli cells were used as phospholipid sources, a cis-trans isomerization was detectable which occurred only in the presence of organic solvents. These results indicate that isolated membranes from Pseudomonas or E. coli cells must contain factors which, activated by the addition of organic solvents, enable and control the cis-trans conversion of unsaturated acyl chains of membrane phospholipids by the periplasmic isomerase.